2019
DOI: 10.1128/jvi.00538-19
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Intra-individual Lentiviral Evolution Rates: a Systematic Review of Human, Nonhuman Primate, and Felid Species

Abstract: Lentiviral replication mediated by reverse transcriptase is considered to be highly error prone, leading to a high intra-individual evolution rate that promotes evasion of neutralization and persistent infection. Understanding lentiviral intraindividual evolutionary dynamics on a comparative basis can therefore inform research strategies to aid in studies of pathogenesis, vaccine design, and therapeutic intervention. We conducted a systematic review of intra-individual evolution rates for three species groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…TM is the immunodominant epitope in FIV that induces the earliest and strongest antibody response in cats experimentally infected with FIV [53,62,63,71,72]. Although the evolutionary rate of FIV is rather slow when compared to other lentiviruses [85] and seems to be dependent on the virus strain and the infection stage [86], it has been shown that the preferred genetic location for recombination is in the envelope ( env ) gene, which also encodes TM [10,25,61,87]. Additionally, low fidelity in the transcription process and a change in the clade distribution could have contributed to the increased variability of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…TM is the immunodominant epitope in FIV that induces the earliest and strongest antibody response in cats experimentally infected with FIV [53,62,63,71,72]. Although the evolutionary rate of FIV is rather slow when compared to other lentiviruses [85] and seems to be dependent on the virus strain and the infection stage [86], it has been shown that the preferred genetic location for recombination is in the envelope ( env ) gene, which also encodes TM [10,25,61,87]. Additionally, low fidelity in the transcription process and a change in the clade distribution could have contributed to the increased variability of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, feline models using cats infected with immunodeficiency virus (FIV) also served as models of naturally occurring immunodeficiency [ 29 ]. However, because FIV infection does not reproduce all the features of HIV infection and some important aspects differ markedly between cats and humans, this model is rarely used [ 4 , 30 ]. Mice, rats, or rabbits were originally proposed, but they could not be successfully infected with HIV [ 4 , 31 , 32 ].…”
Section: Animal Models Used For Research On Hiv Curementioning
confidence: 99%
“…ApharSeq utilizes sequencing for the detection of viral molecules, and as such it is well suited to variant calling. A common hurdle in amplicon-based genotyping assays, especially in the case of viruses that might manifest multiple minor variants in the same host, is the inability to distinguish between PCR and sequencing errors from underlying genotype variants (32,33). Unlike other common viral genome sequencing protocols (34,35), ApharSeq incorporates a unique molecular identifier (UMI) at the reverse transcription step.…”
Section: Identifying Viral Variants In Clinical Samples With Apharseqmentioning
confidence: 99%